Divergent synthesis of fused Benzo-xanthene and oxazine derivatives via Cu-catalyst - Meshari A Alsharif; Naseem Ahmed; Mohammed Issa Alahmdi; Sayeed Mukhtar; Humaira Parveen; Rami J. Obaid; Abdulraheem S.A. Almalki (Journal of Saudi Chemical Society)
Cu-Cu2O combination showed synergic effects in catalyzing intramolecular Ullmann coupling reaction for halo-Betti bases to afford fused benzo-xanthenes from both electron-rich and electron-deficient aromatic systems in good yield under mild reaction conditions. The sterically hindered halo-Betti bases also provided products in excellent yield. Under optimized condition, a gram scale reaction was also performed to afford the product in excellent yield. However, without ortho-halo substituted Betti-bases failed to afford fused benzo-xanthene derivatives. Exploring the reaction optimization without Cu metal, serendipitously it was produced 1,3-oxazine derivatives in excellent yield via intramolecular cross-dehydrogenative coupling (CDC) reaction. Similarly, electron-rich, electron-deficient and sterically hindered Betti-bases provided the products in good to excellent yield under mild condition.